Estudo da produção de biopolímeros polihidroxialcanoatos por bactérias isoladas do inseto-praga Diabrotica speciosa - Pires, Marília Silva (2023)
Petroleum-derived plastic materials are fundamental in our daily lives due to characteristics such as strength and durability. However, the indiscriminate use of these materials is one of the main causes of environmental problems, since these materials are not biodegradable and accumulate in the environment. Biopolymers produced by microorganisms are an alternative to replace conventional plastic materials, being of renewable origin, biodegradable and, even so, presenting properties similar to those of synthetic polymers and suitable for several industrial applications. In this context, the objective of this work was to study the production of PHAs biopolymers by Deftia sp. and Aureimonas sp. using different culture media and substrates, as well as describing aspects of the genome organization of these strains based on the production of PHAs. The analysis of the genome of the two bacteria allowed the identification of possible genes involved in the biosynthesis of PHAs, such as phaA, phaB and phaC. The behavior related to cell growth, production and composition of PHAs of these strains in different culture media (complex medium and saline medium) and using different substrates, such as whey, glycerol, lignin and vegetable oil, was evaluated. The PHAs produced for each condition were characterized in terms of monomeric structure and composition by gas chromatography coupled to mass spectrometry. The results showed variability in the monomeric composition and cell growth depending on the culture medium used, with emphasis on the cultivation of Deftia sp. in complex medium with glycerol, which showed the monomers 3-HB, 3-HV, 3-HO and 3-HD in the PHA produced and cell growth of 2,34 g/L. An analytical method was developed by GC-MS for the quantitative analysis of 3-HB monomer and showed satisfactory results of the validation parameters. With that, a multivariate analysis was used to determine the variables that most influence the process of cell growth and PHAs production, based on the selection of the best conditions established in the evaluation of the culture media for each bacterium. The variables substrate concentration, cultivation time and oxygenation of the medium were influential on the bioprocess. The best cultivation conditions showed values of 4,30 g/L, 1,19×10-1 g/L and 2,77% for cell growth, polymer concentration and yield, respectively, for Deftia sp. in complex medium with glycerol and 2,60 g/L, 1,30×10-1 g/L and 4.98% in whey medium. For Aureimonas sp. grown in whey the best conditions showed values around 1,51 g/L, 7,60×10-1 g/L and 5,05%. In this study, it was possible to perceive the potential of the strains to produce PHAs using different substrates, evidencing and highlighting the possible use of low-cost carbon sources for the production of molecules with high added value.